Solution-Based Ultraviolet Photodiode with ZnO Nanoparticle/Poly(3,4-Ethylenedioxythiophene) Polystyrene Sulfonate Heterojunction and Negative Capacitance - Jin Li; Xin Chang; Shunpu Li; Yi Zhang; Daping Chu (Advanced Devices & Instrumentation)
Ultraviolet (UV) detectors have been widely applied to extensive fields, such as photoelectric microsensors, UV imaging, optical communications, and biological detection. The demand for high-performance UV detectors with low cost and easy fabrication drives the development of novel materials and structures such as wide-bandgap semiconductors, polymers, photodiodes, and phototransistors. Here, we demonstrate a new UV photodiode implemented using solution-processing-based zinc oxide (ZnO) nanoparticles (NPs) and a poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) heterojunction. Moreover, the fabrication process is simple and suitable for large-scale production. First, solution-based films of ZnO NPs and PEDOT:PSS were prepared, and their optical and electrical properties were individually characterized. Strong optical absorption by ZnO NPs for wavelengths below 400 nm was experimentally observed, while absorption by PEDOT:PSS in the same wavelength range is trivial. The ZnO-NPs-PEDOT:PSS heterojunction was then characterized for its electrical rectification behavior and photoresponse, from which a potential barrier height of 0.64 eV and UV current gain of 91.2 were determined. The resistor–capacitor time constant was also calculated to be 946.46 ms at zero bias, and its dependence on reverse bias voltage was determined. Finally, negative capacitance was first observed in this kind of heterojunctions under forwarding bias, which was further investigated regarding a threshold effect and transition frequency. This new type of UV photodiodes based on ZnO-NPs-PEDOT:PSS heterojunctions is highly promising for high-resolution applications, such as ZnO NPs-based spatial light modulators (SLMs), where the ascendant properties of the heterojunction can be fully utilized to achieve the high-resolution capability of optically addressed SLMs.